2003
DOI: 10.1097/00000542-200304000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Parecoxib Sodium, a Parenteral Cyclooxygenase 2 Selective Inhibitor, Improves Morphine Analgesia and Is Opioid-sparing following Total Hip Arthroplasty

Abstract: Administration of parecoxib sodium with PCA morphine resulted in significantly improved postoperative analgesic management as defined by reduction in opioid requirement, lower pain scores, reduced time on PCA morphine, and higher Global Evaluation ratings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
96
2
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(107 citation statements)
references
References 28 publications
4
96
2
5
Order By: Relevance
“…Furthermore, coadministration of celecoxib with morphine provides analgesia even after 14 days of treatment, suggesting that celecoxib may have a salutary effect on opioid analgesia. Cyclooxygenase-2 inhibition may at least partly explain the clinical improvements in postoperative pain control that have been seen with a combination of opioids and COX-2 inhibitors and/or NSAIDs (Kroin et al, 2002;Malan et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, coadministration of celecoxib with morphine provides analgesia even after 14 days of treatment, suggesting that celecoxib may have a salutary effect on opioid analgesia. Cyclooxygenase-2 inhibition may at least partly explain the clinical improvements in postoperative pain control that have been seen with a combination of opioids and COX-2 inhibitors and/or NSAIDs (Kroin et al, 2002;Malan et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Parecoxib is the parenteral prodrug of the selective COX-2 inhibitor valdecoxib and is widely used outside of the United States for acute and perioperative pain. 65 A placebo-controlled randomized study of intravenous parecoxib sodium (3 days) followed by oral valdecoxib (7 days) in 1671 patients who had undergone coronary artery bypass graft surgery 6 showed that patients receiving these agents had a postoperative CV event rate of 2% compared with a rate of 0.5% in patients receiving placebo. Of interest was the finding that 35% of the events in the active treatment group were observed in a 30-day period that followed discontinuation of the parecoxib and valdecoxib.…”
Section: Use Of Parenteral Cox-2 Inhibitors In the Perioperative Periodmentioning
confidence: 99%
“…Most of previous study of parecoxib were on the orthopedic surgery and showed that intravenous parecoxib did reduce the pain score postoperatively (13,14 (15) first carried out a study to find out the effect of parecoxib combined with thoracic paravertebral ropivacaine infusion in thoracotomy. Patients receiving parecoxib (40 mg intravenously used 20 min before extubation and 12 hrs after the procedure) had less pain at rest and during movement compared with those with placebo at 12, 24, and 48 hours after surgery.…”
Section: Discussionmentioning
confidence: 99%